The Endoscopic Lumbar Interbody Fusion: A Narrative Review, and Future Perspective - Pholprajug, Phattareeya; Kotheeranurak, Vit; Liu, Yanting; Kim, Jin-Sung (Neurospine, 2023)
Lumbar interbody fusion stands as a preferred surgical solution for degenerative lumbar spine diseases. The procedure primarily aims to establish lumbar segment stability, directly addressing patient symptoms associated with spinal complications. Traditional open surgery, though effective, is linked with notable morbidities and extended recovery time. To mitigate these concerns, minimally invasive surgery (MIS) has garnered significant popularity, presenting an appealing alternative with numerous benefits such as reduced soft tissue trauma, decreased blood loss, and expedited recovery. Among MIS procedures, full endoscopic spinal surgery, characterized by its minimal invasiveness, holds the potential to further minimize morbidities while enhancing surgical outcomes. Endoscopic lumbar interbody fusion, a novel procedure within this paradigm, has gained attention for offering advantages comparable to those of minimally invasive transforaminal lumbar interbody fusion. However, the safety, efficacy, and associated surgical techniques and instrument design of this method continue to be subjects of ongoing debate. This paper critically reviews current evidence on the safety, efficacy, and advantages of endoscopic lumbar spinal interbody fusion, examining whether it could indeed supersede existing mainstream techniques.